Risk Factors Associated with Prevalence of Candida albicans, Gardnerella vaginalis, and Trichomonas vaginalis among Women at the District Hospital of Dschang, West Region, Cameroon - Vincent Khan Payne; Tsonang Tassongwa Florence Cécile; Yamssi Cedric; Noumedem Anangmo Christelle Nadia; Ouaba José (International Journal of Microbiology)
Background. Vaginal or genitourinary infections are a major cause of morbidity, sterility, and increase in the vulnerability to cancers and HIV/AIDS infection. The aim of this study was to determine the prevalence of vaginal infections of C. albicans, G. vaginalis, and T. vaginalis among women in the locality of Dschang, West Region of Cameroon. Method. A prospective study was carried out in the District Hospital of Dschang. After obtaining informed consent, one thousand and one (1001) samples of vaginal swabs were collected. Biological diagnosis was carried out on fresh samples, Gram stained, and then cultivated in Sabouraud agar in a Petri dish, in order to isolate and identify the various infectious agents. Results. Five hundred and twenty-five (525) women were diagnosed positive, hosting at least one of these microorganisms, making an overall prevalence of 52.44%. Two hundred and fifty-six (256) women (25.57%) were infected with C. albicans, and 171 (17.08%) with G. vaginalis. Ninety-five (9.49%) were infected with both C. albicans and G. vaginalis, 2 (0.20%) with C. albicans and T. vaginalis, and 1 (0.1%) with G. vaginalis and T. vaginalis. Conclusion. Drastic measures should be taken in order to improve life styles to regress the frequency of these infections. Results obtained in this study, will help to educate and shed more light on the prevalence of vaginal infections in the West Region of Cameroon.